Une analyse économétrique de la demande et de l’offre de dépôts des sociétés de crédit populaire : le cas des Caisses populaires - Chateau, Jean-Pierre (L'Actualité économique, 1979)
The aim of the study is to explain Quebec major credit union's deposit market by way of integrating its public demand function with the institution's rate-setting operation. The demand for Caisses' deposits is specified as a dynamic stock adjustment model. On the other hand, the intermediary's rate-setting reduced form is derived from a risk-return portfolio balance model in which the managers maximize the expected utility of reserves. The two models are integrated by means of a liability composite rate.Econometric estimates of the integrated model provide us with interesting policy insights. For instance, the Quebecois public views chartered banks' deposits as a weak substitute for Caisses' deposits; it is also more responsive to nonrate arguments, such as loan eligibility or the institution's ethnic appeal. On the supply side, competitive liability rates are more important than returns on assets when the Caisses set its deposit rate. Finally, the impact growth imbalance between loans and deposits is well captured by a flow variable, without infringing on the steady determination based on rates.